The effect of planting media composition and liquid fertilizer dosage on sand media on the growth of mustard plants (Brassica juncea L.) - Utomo, Basri Wahyu; Ridwan, Ridwan; Amien, Elhamida Rezkia; Asmara, Sandi; Amin, M. (Jurnal Agricultural Biosystem Engineering, 2024)
The aim of this study is to analyze the potential of sand as a planting medium with the addition of cocopeat, obtain the dose of liquid organic fertilizer for sand media, and find the suitable combination of cocopeat for sand media. The method used is a Complete Randomized Design (CRD) Factorial with 2 factors. The first factor is the combination of planting media (sand and cocopeat) and the second factor is the dose of liquid organic fertilizer. The first factor consists of 3 levels: M1 (sand and cocopeat), M2 (sand and cocopeat mixed), and M3 (cocopeat and sand). Each planting medium has a height of 11 cm. The second factor has 3 levels: P1 (LOF 10 ml/l), P2 (LOF 20 ml/l), and P3 (LOF 30 ml/l). The initial stages carried out in this research include preparing the planting media, seed sowing (for approximately ±16 days), transplanting, and maintenance (watering and fertilization). Observations include monitoring every 3 days (plant height, number of leaves, and leaf width) and final observations (total weight of fresh mustard plants, weight of upper and lower mustard plant parts). The planting media (sand, cocopeat) influenced all parameters. The optimum dose of liquid organic fertilizer is a dose of 30 ml/liter. The most optimal interaction of planting media factors with the dose of liquid organic fertilizer is sand media, cocopeat, and a dose of 30 ml (M1P3) with an average total fresh weight of 4.14 grams. Keywords: Cocopeat, LOF, Planting media, Sand.